Synthesis and characterization of Ti3(Al1-nGe n)C2 by a reactive hot pressing of TiCx, Al, and Ge powder mixture - Han, J.-H.; Nam, K.-D.; Park, S.-W.; Kim, Y.-D. (Solid State Phenomena, 2006)
Bulk Ti3(Al-nGen)C2 (n=0, 0.3, 0.5, 0.7, 1.0)were synthesized by a reactive hot pressing of TiCx (x=0.6), Al and Ge powder mixture at 1400°C for 1 h under 25 MPa. A series of Ti 3(Al1-nGen)C2 was successfully synthesised by a hot pressing through a direct liquid-solid reaction between Al-Ge melt and TiCx, and simultaneous densification. Synthesized bulk Ti 3(Al1-nGen)C2 was maintained a typical layered structure as shown in other ternary carbide such as Ti 3AlC2 and Ti3GeC2. With increasing Al or Ge contents in Ti3(Al1-nGen)C 2, both of Vickers hardness and flexural strength of Ti 3(Al1-nGen)C2 were increased compared to those of pure Ti3AlC2 and Ti 3GeC2. The maximum flexural strength of Ti 3(Al1-nGen)C2 (n=0.3) was about 600 MPa, which was about 3 times higher than that of pure Ti3GeC 2. The Vickers hardnesses of Ti3(Al1-nGe n)C2 and Ti3AlC2 were slightly decreased with increasing an indentation load.